2017
DOI: 10.1007/s11938-017-0163-x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and the Pancreatobiliary Diseases

Abstract: Newer cohort studies suggest the presence of diabetes to increase the severity and worsen outcomes in acute pancreatitis. Post pancreatitis diabetes is a novel disease entity being increasingly recognized. The use of pancreatic enzyme replacement therapy (PERT) in chronic pancreatitis may attenuate the risk of endocrine dysfunction. Pancreatic cancer may either be the consequence of diabetes or a presenting manifestation. The use of anti-diabetic medications may confer protection against development of pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…4 Of note, recent literature also associates diabetes with an increased risk for development of pancreatitis. 2729…”
Section: Acute Pancreatitis: a Disorder With Different Causes Requirimentioning
confidence: 99%
“…4 Of note, recent literature also associates diabetes with an increased risk for development of pancreatitis. 2729…”
Section: Acute Pancreatitis: a Disorder With Different Causes Requirimentioning
confidence: 99%
“…In addition to gallstones, women are more likely to have acute pancreatitis due to complications of endoscopic retrograde cholangiopancreatography (ERCP) or an autoimmune cause and are more likely to have idiopathic acute pancreatitis 1. Recent literature suggests that diabetes is associated with a small increase in risk for development of pancreatitis 456…”
Section: Epidemiologymentioning
confidence: 99%
“…In this study, the patients and controls were found to have similar rates of DM. However, this comorbidity is an important factor in carcinogenesis (Shafqet et al, 2017) in that hyperinsulinemia stimulates greater expression of type 1 insulin-like growth factor (IGF-1) and insulin receptors via PI3K/Akt/mTOR signaling, thus triggering proliferation, angiogenesis, metastasis, and inhibition of apoptosis (Wojciechowskaet al, 2016;Labibet al, 2019;Clements et al, 2020). It is important to note that our sample contained a majority of women; however, the global incidence of DM among men has risen in recent decades (NCD Risk Factor Collaboration, 2016).…”
Section: Discussionmentioning
confidence: 99%